Cooperative communications for improved wireless network transmission framework for virtual antenna array applications - Uysal, Murat, 1973-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
Cooperative communications for improved wireless network transmission: framework for virtual antenna array applications provides practitioners, researchers, and academicians with fundamental principles of cooperative communication, presenting the latest advances in this rapidly evolving field. Containing research from leading international experts, this Premier Reference Source offers readers diverse findings and exposes underlying issues in the analysis, design, and optimization of wireless systems.
15. Single-carrier frequency domain equalization for broadband cooperative communications / Tae-Won Yune, Dae-Young Seol, Dongsik Kim, Gi-Hong Im -- 16. Applications of majorization theory in space-time cooperative communications / Aydin Sezgin, Eduard Jorswieck -- 17. Data gathering in correlated wireless sensor networks with cooperative transmission / Laxminarayana Pillutla, Vikram Krishnamurthy -- 18. Cooperative broadcast in large-scale wireless networks / Birsen Sirkeci-Mergen, Anna Scaglione, Michael Gastpar -- 19. Cooperative communication system architectures for cellular networks / Mischa Dohler, Djamal-Eddine Meddour , Sidi-Mohammed Senouci, Hassnaa Moustafa.
Includes bibliographical references (p. 548-583) and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: Wireless communication systems; Antenna arrays; Broadband cooperative communications; Coding schemes; Cooperative communications; Distributed transmit; Energy efficient communication; Mathematical tools for cooperative networks; Receive diversity techniques; Relay selection; Virtual antenna array applications; Wireless network transmission; Electronic books